The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1115/1.4027615
|View full text |Cite
|
Sign up to set email alerts
|

Shear Behavior of Bovine Scleral Tissue

Abstract: Ocular tissue properties have been widely studied in tension and compression for humans and a variety of animals. However, direct shear testing of the tissues of the sclera appear to be absent from the literature even though modeling, analyses, and anatomical studies have indicated that shear may play a role in the etiology of primary open angle glaucoma (POAG). In this work, the mechanical behavior of bovine scleral tissue in shear has been studied in both out-of-plane and in-plane modes of deformation. Stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
2
2
0
Order By: Relevance
“…Though this relationship is well-characterized for tendons, ligaments, cornea and other tissues [2, 24-26, 28, 45], it remains still not fully characterized on sclera. Our results herein are consistent with our previous cross-sectional study of collagen waviness in ONHs fixed at various IOPs [16] and with those of other groups [46, 47].…”
Section: Discussionsupporting
confidence: 93%
“…Though this relationship is well-characterized for tendons, ligaments, cornea and other tissues [2, 24-26, 28, 45], it remains still not fully characterized on sclera. Our results herein are consistent with our previous cross-sectional study of collagen waviness in ONHs fixed at various IOPs [16] and with those of other groups [46, 47].…”
Section: Discussionsupporting
confidence: 93%
“…An important result from this study was the quantification of shear strains in the intact peripapillary sclera during increases of IOP. Using shear testing on dissected bovine scleral specimens, a previous study showed that the posterior sclera had a stiffer response to in-plane shear compared to out-of-plane shear [33]. Our results showed that the maximum shear was primarily out-ofplane (in the planes formed by the meridional and throughthickness directions) and at an angle about 45 deg to the scleral surface ( Fig.…”
Section: Discussionsupporting
confidence: 49%
“…The variations in matrix composition would most likely contribute to spatial variations in the matrix stiffness that were ignored in our model. In a recent study characterizing the shear behavior of the bovine sclera, Argento et al [ 50 ] showed that the in-plane shear modulus was 50% larger in the peripheral sclera than in the peripapillary sclera. Assuming position-dependent matrix and collagen fibers stiffness in our model would have considerably increased the computational cost of the inverse method may have led to the existence of multiple minima to the cost function.…”
Section: Discussionmentioning
confidence: 99%